2016
DOI: 10.1093/femsyr/fow080
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiaemetabolism in ecological context

Abstract: The architecture and regulation of Saccharomyces cerevisiae metabolic network are among the best studied owing to its widespread use in both basic research and industry. Yet, several recent studies have revealed notable limitations in explaining genotype–metabolic phenotype relations in this yeast, especially when concerning multiple genetic/environmental perturbations. Apparently unexpected genotype–phenotype relations may originate in the evolutionarily shaped cellular operating principles being hidden in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 103 publications
0
30
0
3
Order By: Relevance
“…However, it is important to highlight that in theses reconstructions, it is not considered that cells may need time to adapt to genetic perturbations or environmental variability [ 79 ]. Additionally, yeast interactions with other microorganisms and the secretion of compounds that can influence their surrounding environment are not taken into account [ 81 ]. Despite these inaccuracies, genome-scale metabolic reconstructions have proved to be very efficient discovering new drug targets, and once a model is built, drug targets can be predicted relatively easily.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to highlight that in theses reconstructions, it is not considered that cells may need time to adapt to genetic perturbations or environmental variability [ 79 ]. Additionally, yeast interactions with other microorganisms and the secretion of compounds that can influence their surrounding environment are not taken into account [ 81 ]. Despite these inaccuracies, genome-scale metabolic reconstructions have proved to be very efficient discovering new drug targets, and once a model is built, drug targets can be predicted relatively easily.…”
Section: Resultsmentioning
confidence: 99%
“…This species seems not to be able to respond efficiently to increasing nitrogen concentrations. Contrarily, it has been argued that S. cerevisiae does not show adaptations to any particular habitat, but rather an ability to survive in a wide range of conditions (Goddard and Greig, 2015) which is consistent with its life history of nomadic generalist that inhabits diverse niches (Jouhten et al, 2016;Liti et al, 2009). Interestingly, it has also been demonstrated that one genomic region that shows strong differentiation between the oak and wine European populations of S. cerevisiae correspond to a gene coding for a transporter for oligopeptides that can act as nitrogen sources in wines (Marsit et al, 2015).…”
Section: Low Temperature and Low Nitrogen Concentration Favourmentioning
confidence: 93%
“…The population structure of S. cerevisiae strains from other habitats has already been studied. Strains isolated from soil, bark, fruits, fermented beverages, and vectors, such as Drosophila, bees, wasps, or humans, have been studied at the genetic level (Goddard & Greig, 2015;Jouhten, Ponomarova, Gonzalez, & Patil, 2016). Recently, whole genome studies comparing tens, hundreds, and now thousands of strains from natural and man-made environments have emerged and provided insights into yeast domestication (Almeida et al, 2015;Fay & Benavides, 2005;Gallone et al, 2016;Gonçalves et al, 2016;Legras et al, 2018;Libkind et al, 2011;Liti et al, 2009;Ludlow et al, 2016;Peter et al, 2018;Schacherer, Shapiro, Ruderfer, & Kruglyak, 2009).…”
Section: Genus Kazachstaniamentioning
confidence: 99%